A Framework for Successful CRM Implementation in Indian Banking Sector - Pawan Kumar Gupta (International Journal of Engineering and Management Research, 2023)
Banking sector is a pivot of economy & also plays vital role for boosting GDP rate in Indian economy. It is highly required that customer should delight after perceiving services in banking sector. As well as financial inclusion is spreading, the need of maintain good relationship with customers is also increasing after implementation of financial inclusion scheme. In India, most of people have covered by financial inclusion but still one thing remains, how can bank maintain good relationship with existing customer & prospective customer? Good relationship with customers is main key for boosting growth rate of country. If banks get success for creating good relationship with customers, in fact it will be great achievement for country. CRM is always circumspect for good relationship. It provides healthy financial track for running banking sector in economy, but successfully implementation for CRM is more important term to boost growth rate of country. Indian banking sector is backbone of economy. We can’t ignore it for the development of economy but now banking sector is facing hyper competition in present scenario. Indian banking sector is passing through critical stage & facing a lot of changes. With help of successfully CRM implementation in Indian banking sector, we can solve this problem with easy way and also generate sound banking in country. According to RBI, “CRM is a continuous process – it is a journey, not a destination. To be successful in this arena, banks need to embrace CRM as a philosophy and adopt a strategy for managing customer relationships that effectively address three key areas: people, processes and technology and even in the context of financial stability, CRM is important.” CRM model in banking sector must integrate of technological adaptation, organise training & skill development programme, collection of customer data, analysis & interpretation, timely integration and evaluation for achieving the goal.